High photocatalytic activity of Fe2O3/TiO2 nanocomposites prepared by photodeposition for degradation of 2,4-dichlorophenoxyacetic acid - Shu Chin Lee; Hendrik O. Lintang; Leny Yuliati (Beilstein Journal of Nanotechnology, 2017)
Two series of Fe2O3/TiO2 samples were prepared via impregnation and photodeposition methods. The effect of preparation method on the properties and performance of Fe2O3/TiO2 for photocatalytic degradation of 2,4-dichlorophenoxyacetic acid (2,4-D) under UV light irradiation was examined. The Fe2O3/TiO2 nanocomposites prepared by impregnation showed lower activity than the unmodified TiO2, mainly due to lower specific surface area caused by heat treatment. On the other hand, the Fe2O3/TiO2 nanocomposites prepared by photodeposition showed higher photocatalytic activity than the unmodified TiO2. Three times higher photocatalytic activity was obtained on the best photocatalyst, Fe2O3(0.5)/TiO2. The improved activity of TiO2 after photodeposition of Fe2O3 was contributed to the formation of a heterojunction between the Fe2O3 and TiO2 nanoparticles that improved charge transfer and suppressed electron–hole recombination. A further investigation on the role of the active species on Fe2O3/TiO2 confirmed that the crucial active species were both holes and superoxide radicals. The Fe2O3(0.5)/TiO2 sample also showed good stability and reusability, suggesting its potential for water purification applications.